KERAGAMAN DAN KELIMPAHAN LEBAH SOSIAL (APIDAE) PADA BUNGA TANAMAN PERTANIAN MUSIMAN YANG DIAPLIKASI PESTISIDA DI JAWA BARAT - Kahono, Sih; Erniwati, Erniwati (BERITA BIOLOGI, 2014)
Study of diversity and abundance of social bees (Apidae) in the pesticide-applied seasonal crops were carried out for nine species of crops in a lowland area, Dramaga, Bogor and on 17 species of crops ina highland area, Lembang, Bandung, both in the province of West Java. Two species of honey bees (Apis cerana and A. dorsata) and one species of stingless bee (Trigonalaeviceps) were recorded from the lowland crops,while only A. cerana was found in the highland crops. The most abundant bee species on both low and highland was the honey bee A. cerana. The number of A. cerananests and T. laevicepsnests in the surroundings of the study sites were relatively high. Colony members of both bee species were very active to collect nectar and pollen from flowers in non-pesticide-applied sites; however, the density of bees visiting flowers in pesticide-applied seasonal crops in both lowland and highland were relatively low.